2013
DOI: 10.14434/josotl.v14i1.3327
|View full text |Cite
|
Sign up to set email alerts
|

Examining the literacy histories of doctoral students in an educational studies program through surveys and interviews: A mixed methods study

Abstract: The purpose of this mixed methods sequential explanatory study was to explain the relationship between literacy experiences over time and the literacy identities of the doctoral students in a teacher education and higher education program. The quantitative phase, surveying 36 participants, revealed a positive correlation between participant's present and past literacy experiences, suggesting that past literacy experiences impacted their present perception of themselves as successful doctoral students. In the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It does not come as a surprise that doctoral students have positive literacy identities and literacy histories, however, survey data revealed that some doctoral students did not have positive literacy identities and histories (Adams-Budde, Howard, Jolliff, & Myers, 2014). For this reason, we chose to highlight two participants that held these qualities in order to examine how their previous experiences shaped their current positive literacy identities with the hopes of promoting positive self-perceptions and providing these experiences for all students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It does not come as a surprise that doctoral students have positive literacy identities and literacy histories, however, survey data revealed that some doctoral students did not have positive literacy identities and histories (Adams-Budde, Howard, Jolliff, & Myers, 2014). For this reason, we chose to highlight two participants that held these qualities in order to examine how their previous experiences shaped their current positive literacy identities with the hopes of promoting positive self-perceptions and providing these experiences for all students.…”
Section: Discussionmentioning
confidence: 99%
“…An individual's sense of self, or identity, can be understood through stories (McAdams, 1993;McKinney & Giorgis, 2009) and visual representations (Adams-Budde, Howard, Jolliff, & Myers, 2014;Bustle, 2004;Georgakopoulou, 2007). Moreover, individuals are engaged in the process of identity construction through the telling of these stories and the creation of visual representations.…”
Section: Literacy Stories and Representations Of Literacy Identitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that identity stories can take many forms such as interviews (Drake et. al, 2001) artistic representations (Adams-Budde, Howard, Jolliff, & Myers, 2014;Howard et. al, 2017;Bustle, 2004;Hayik, 2012;Ives & Juzwik, 2015) and narratives (Williams, 2003).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…al, 2017;Bustle, 2004;Hayik, 2012;Ives & Juzwik, 2015) and narratives (Williams, 2003). Adams-Budde, Howard, Jolliff, & Myers, 2014 asked participants to create visual representations of their literacy identities and then to discuss these representations with researchers as a means of sharing their literacy stories. The visual representations from the presentations showcased that participants valued reading and writing a range of texts including religious texts, Internet sources, academic texts, etc.…”
Section: Review Of the Literaturementioning
confidence: 99%